2014
DOI: 10.1371/journal.pone.0105313
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin Cytoplasmic Domains Inhibit the Cell Surface Localization of Endogenous E-Cadherin, Blocking Desmosome and Tight Junction Formation and Inducing Cell Dissociation

Abstract: The downregulation of E-cadherin function has fundamental consequences with respect to cancer progression, and occurs as part of the epithelial–mesenchymal transition (EMT). In this study, we show that the expression of the Discosoma sp. red fluorescent protein (DsRed)-tagged cadherin cytoplasmic domain in cells inhibited the cell surface localization of endogenous E-cadherin, leading to morphological changes, the inhibition of junctional assembly and cell dissociation. These changes were associated with incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 54 publications
4
54
0
Order By: Relevance
“…Consistent with the published study and our prediction, the level of β‐catenin colocalized with N‐cadherin greatly decreased to ~25% in cells expressing either CTF variant relative to the GFP control (Figure D). On overexpression of the CTF constructs, the abundance of N‐cadherin at the membrane was also reduced to ~60% (Figure C), which is consistent with a role of β‐catenin in stabilizing N‐cadherin at the membrane . Using the same approach, we found a significant ~2.75‐fold increase of μ2 colocalized with N‐cadherin at plasma membrane in cells overexpressing the YDSL/YDYL mutant as compared with expressing the WT or RR mutant CTF (Figure E,F, original image in Figure S4), indicating that YDSL/YDYL CTF mutant sequestered β‐catenin and not μ2 to increase the binding of μ2 to N‐cadherin at the membrane.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Consistent with the published study and our prediction, the level of β‐catenin colocalized with N‐cadherin greatly decreased to ~25% in cells expressing either CTF variant relative to the GFP control (Figure D). On overexpression of the CTF constructs, the abundance of N‐cadherin at the membrane was also reduced to ~60% (Figure C), which is consistent with a role of β‐catenin in stabilizing N‐cadherin at the membrane . Using the same approach, we found a significant ~2.75‐fold increase of μ2 colocalized with N‐cadherin at plasma membrane in cells overexpressing the YDSL/YDYL mutant as compared with expressing the WT or RR mutant CTF (Figure E,F, original image in Figure S4), indicating that YDSL/YDYL CTF mutant sequestered β‐catenin and not μ2 to increase the binding of μ2 to N‐cadherin at the membrane.…”
Section: Resultssupporting
confidence: 72%
“…N-cadherin at the plasma membrane was first labeled with an antibody against its extracellular domain, then we used different fluorophore-tagged secondary antibodies to distinguish the surface and internalized population of N-cadherin as described. 12 Consistent with the previous finding that overexpressed cadherin CTF decreased the surface population of cadherin, 36,38 the surface population of endogenous Ncadherin was reduced (16% reduction) in neurons expressing the CTF constructs as compared with the GFP control ( Figure 8B). However, colocalization of the iNcad and EEA1 was enhanced~48% in neurons expressing the YDSL/YDYL mutant but not other CTF variants or GFP ( Figure 8C), which reflects an increased clathrin-mediated N- uncoupled from CTF sequestration contribute to a small but significant increase on the CME pool of N-cadherin that traffic to the early endosome.…”
Section: Increased N-cadherin Endocytosis Promotes Neurite Outgrowtmentioning
confidence: 92%
See 1 more Smart Citation
“…We made a chimeric construct (DNCT) comprising a fluorescent protein, DsRed, the N-cadherin cytoplasmic domain (NCT), and a C -terminal FLAG tag 25 . The construct was expressed under the control of a Tet-repressible transactivator in an MDCK cell clone T23 expressing the tet repressor (DNCT+ cells).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we showed that Discosoma sp. red fluorescent protein (DsRed)-tagged cadherin cytoplasmic domains expressed in MDCK cells interact with β-catenin, reduce the β-catenin levels associated with endogenous E-cadherin, and inhibit the cell surface localization of endogenous E-cadherin, leading to morphological changes, including the inhibition of desmosome and tight junction formation and a reduction in the mechanical integrity of the epithelial cell sheets 25 . Contrary to previous observations that expression of the cadherin cytoplasmic domains inhibited cell growth by inhibiting β-catenin signaling, we found that expression of the cytoplasmic domains increased cell proliferation.…”
mentioning
confidence: 99%